CO2 recycling by phosphoenolpyruvate carboxylase enables cassava leaf metabolism to tolerate low water availability - Punyasu, Nattharat; Kalapanulak, Saowalak; Saithong, Treenut (Frontiers in Plant Science, 2023)
Cassava is a staple crop that acclimatizes well to dry weather and limited water availability. The drought response mechanism of quick stomatal closure observed in cassava has no explicit link to the metabolism connecting its physiological response and yield. Here, a genome-scale metabolic model of cassava photosynthetic leaves (leaf-MeCBM) was constructed to study the metabolic response to drought and stomatal closure. As demonstrated by leaf-MeCBM, leaf metabolism reinforced the physiological response by increasing the internal CO2 and then maintaining the normal operation of photosynthetic carbon fixation. We found that phosphoenolpyruvate carboxylase (PEPC) played a crucial role in the accumulation of the internal CO2 pool when the CO2 uptake rate was limited during stomatal closure. PEPC mechanistically enhanced drought tolerance in cassava by providing sufficient CO2 for carbon fixation by Rubisco, resulting in high production of sucrose in cassava leaves. The metabolic reprogramming decreased leaf biomass production, which may lead to maintaining intracellular water balance by reducing the overall leaf area. This study sheds light on how the metabolic and physiological responses act in concert to boost tolerance, growth, and production in drought conditions.